Perilaku Muzakki dalam Membayar Zakat Mal (Studi Fenomenologi Pengalaman Muzakki di Kota Kendari) - Bachmid, Gamsir (Jurnal Aplikasi Manajemen, 2012)
The purpose of this research are: 1) to reveal and give meaning towards muzakki belief on malzakah as obligation, 2) to find out and give meaning towards muzakki behavior in fulfilling mal zakah, and3) give meaning towards phenomenon perceived by muzakki as feedback or impact of obeying mal zakahpayment. The method of analysis used qualitative approach, by using Schultz phenomenological analysis.By exploring this approach, phenomenon was given wide space to reveal its own, through analytical knife'because of motives'and'order to motives'.Based on phenomenon and the meaning, it is stated majorproposition as follow: 1) the forms of values that are expected to bring into reality by muzakki are spiritual,economic, humanity and moral/psychological value; 2) expand the zakah benefit (mashlahah) is the mainpurpose of muzakki behavior, and it is determined by existence of trusted management institution; and 3)zakah fulfilled consistently is alternative strategy to develop wealth, maintain healthy, keep the safety andcreate smart descent.